Peran Pemuda Dalam Pembangunan Desa - Arif Reynaldi; Ibrahim Khan; Krisnawati (Anotero Lembaga Scientific Pekanbaru, 2021)
So many young people have paradigm to change their live must migrate to big cities. This paradigm must be abandoned immediately. Therefore building a village is a fixed price that must be realized immediately. All elements of the village and the community must work together to realize wise and wise village development. The right village potential to become village movers is youth. Youth works to build a civilization, it is time for youth to be the locomotive of that change, so that they become a civilized nation. devotion in the true village among youth. The purpose of this service is to find out about the role of youth in development in a village. The object of this research is 100 youths and this study uses a questionnaire method with data analysis using statistical techniques. that all the variables that determine the effectiveness of the role of youth in village development are in the good and very good categories so that they are worthy of being used as instruments for the assessment of the role of youth in services.